50‐Hz MF does not affect global DNA methylation of SH‐SY5Y cells treated with the neurotoxin MPP+. Issue 1 (7th December 2018) - Benassi, Barbara; Santangeli, Stefania; Merla, Caterina; Tarantini, Letizia; Bollati, Valentina; Butera, Alessio; Marino, Carmela; Consales, Claudia
Abstract : Exposure to extremely low frequency magnetic fields (ELF‐MFs) has been associated with an increased risk of neurodegenerative disorders. The underlying mechanisms, however, are still debated. Since epigenetics play a key role in the neurodegenerative process, we investigated whether exposure to ELF‐MF (50 Hz, 1 mT) might affect global DNA methylation of SH‐SY5Y dopaminergic‐like neuroblastoma cells. We assessed the percentage of 5‐methylcytosine (5‐mC) of three repetitive interspersed sequences (ALU, LINE‐1, or SATα), through pyrosequencing analysis. We demonstrated that ELF exposure (up to 72 h) does not induce any change in the methylation pattern of ALU, LINE‐1, and SATα in both proliferating and differentiated SH‐SY5Y cells. Furthermore, when administered in combination with 1‐methyl‐4‐phenylpyridinium (MPP + ), a neurotoxin mimicking the Parkinson's Disease (PD) phenotype, ELF‐MF exposure does not trigger any modulation in the percentage of 5‐mC of the repetitive elements. Our findings demonstrate that exposure to 50‐Hz MF does not affect global DNA methylation in proliferating and dopaminergic differentiated SH‐SY5Y cells, either under basal culture conditions or under neurotoxic stress. Bioelectromagnetics. 40:33–41, 2019. © 2018 Bioelectromagnetics Society.